Probabilistic Inventory Models With Pareto Distribution - الزبيدي, علي خليل (Journal of Economics and Administrative Sciences, 2011)
Inventory or inventories are stocks of goods being held for future use or sale. The demand for a product in is the number of units that will need to be removed from inventory for use or sale during a specific period. If the demand for future periods can be predicted with considerable precision, it will be reasonable to use an inventory rule that assumes that all predictions will always be completely accurate. This is the case where we say that demand is deterministic.The timing of an order can be periodic (placing an order every days) or perpetual (placing an order whenever the inventory declines to units).in this research we discuss how to  formulating inventory model with probabilistic capital and area constraints with pareto distribution.